Nurse's role in oncology palliative care during the active dying process (Research, Society and Development, 2024)
Introduction: Cancer, the second leading cause of death worldwide, is characterized by the uncontrolled proliferation of cells with the potential for invasion and metastasis. In Brazil, the National Cancer Institute (INCA) estimates approximately 704,000 new cases annually through 2025. As the disease progresses, palliative care aims to control symptoms and improve quality of life, with a multidimensional approach that includes physical, emotional, and spiritual aspects. Objective: To identify the role of nursing professionals in the dying process of patients in palliative care and the necessary competencies for the oncology treatment of patients in the active dying phase. Methods: Narrative literature review based on 10 articles published between 2019 and 2024 on the SciELO, Lilacs, and BVS platforms, as well as guidelines from the Ministry of Health and WHO. Results: Nurses face emotional challenges when dealing with emotional bonds with patients and their families, highlighting the need for institutional psychological support and continuous training. Holistic care and multidisciplinary collaboration are essential for humanized and integrated care; however, a significant knowledge gap regarding the active dying phase and the personal preparation for this stage was focused. Conclusion: The lack of information on managing the active dying phase underscores the importance of continuing education, the practice review, and an empathetic approach, respecting the patient's advance directives.